Questioning the prognostic role of BAP-1 immunohistochemistry in malignant pleural mesothelioma: A single center experience with systematic review and meta-analysis. (August 2020) - Cantini, Luca; Pecci, Federica; Murrone, Alberto; Tomasetti, Marco; Copparoni, Cecilia; Fiordoliva, Ilaria; Morgese, Francesca; Rinaldi, Silvia; Mazzanti, Paola; Rubini, Corrado; Cimadamore, Alessia; Barbisan, Francesca; et al.
Highlights: Loss of BAP1 nuclear staining has been prevalently described in epithelioid MPM. The prognostic value of BAP1 expression in MPM still represents a matter of debate. BAP1 loss was not independently associated with a different risk of all-cause mortality. Abstract: Introduction: The prognostic role of BRCA1 associated protein-1 (BAP1) expression in malignant pleural mesothelioma (MPM) is a matter of debate. We aimed to clarify whether MPM patients with loss of BAP1 expression have better overall survival (OS) compared to BAP1 positive patients. Methods: BAP1 immunohistochemical staining of tumor samples from 60 MPM patients treated at our institution with first-line chemotherapy was evaluated. A systematic literature search was also performed. Only cohort studies that investigated BAP1 by immunohistochemistry (IHC) and reported hazard ratio (HR) values for OS obtained through multivariate analysis (or adjusted for histotype) were considered. A dataset comprising 638 MPM patients was added to our cohort and included in the meta-analysis. Results: In our cohort, 23 samples (38 %) were BAP1 positive/retained (≥1 %) and 37 samples (62 %) were BAP1 negative/loss. BAP1 loss was associated with epithelioid histotype ( p 0.01). Median OS times were 14.8 months (95 % CI: 10.7–29.3) and 18.1 months (95 % CI: 11.2–25.8) for negative and positive BAP1 expression, respectively ( p 0.2). At multivariate analysis, again no differences were observed among the two groups ( p 0.81). Similarly, the meta-analysis consisting of 698 patients showed no difference in terms of OS according to BAP1 status (HR 1.11; 95 % CI, 0·76-1·61; p 0.60). Conclusions: BAP1 expression is not an independent prognostic factor for MPM patients and it should not be considered without taking into account tumor histotype. Future studies should investigate its predictive role in patients treated with new emerging therapies such as immunotherapy.